Radiochemical data for manganese crust sample CYP-74-26-12 - Claude Lalou (PANGAEA, 2023)
Scoriaceous Mn crust fragments on travertine-like nontronite deposit were retrieved near two hydrothermal vents while surveying the rift valley of the Mid-Atlantic Ridge using the diving saucer "CYANA". They have been examined with SEM and with an EDAX (X-ray energy dispersive analysis) apparatus coupled to SEM. Fifteen successive thin layers were taken from the upper surface downward. They were totally dissolved in HCl-HF-HClO4 and spiked with 232U and 228Th as yield tracers. Thin sources of purified U::and Th were prepared and counted by alpha spectrometry.